Divisibilidade e congruência em somatórios - Santos, Raul Rodrigues dos (2018)
This dissertation will present a proposal of Arithmetic teaching, starting from the initial years of Education to Higher Education. The reader will find in this work the following contents: Topics of the History of Mathematics, Arithmetic Progressions, Divisibility, Congruence and Summaries. In the sections, we will have examples solved and proposed activities to be solved by the reader. We have two objectives in this research, the first one is to present a proposal that interrelates mathematical contents of Arithmetic, knowing some historical curiosities and demonstrating Theorems, Propositions, Corollaries, solving examples and questions of the Brazilian Games of Mathematics of the Public Schools (OBMEP). And the second is to propose two Theorems and two Corollas of divisibility and congruence. The theorems, definitions, corollaries, demonstrations and etc. of this bibliographical research were, to a large extent, based on established authors as [12], [14], [16], [17], [18], [19], [20], [22] e [23].